Leeching as Salvage Venous Drainage in Ear Reconstruction: Clinical Case and Review of Literature. Issue 11 (November 2018) - Facchin, Federico; Lancerotto, Luca; Arnež, Zoran Marij; Bassetto, Franco; Vindigni, Vincenzo
Abstract : Background: Ear avulsion is a rare complication of different traumas, such as car accidents, human or animal bites and stab wounds, and can result in dramatic cosmetic consequences for the patient. Ear replantation, revascularization, and reattachment are the options offering best aesthetic results. But venous outflow insufficiency is responsible for a high rate of failures. Leeching is one the most efficient methods to relieve venous congestion. It has been used as an alternative venous outflow in case of severe impairment of the physiologic one. Methods: We present a case of successful rescue of a congested reattached ear by leeching after subtotal avulsion, along with a review of the literature on cases of avulsed auricle reconstruction salvaged by hirudotherapy. Data were collected and analyzed to identify a best regimen to deal with venous congestion. Results: More than 130 cases of avulsed auricle savage are described in the literature, in a fourth of which leech therapy was used in the management of venous congestion. Discussion: In case of both venous outflow deficit or absence, leeches are a potentially successful option to correct the congestion while new veins reestablish normal physiology. The need for anticoagulant/antiaggregant therapy, antibiotics, and often blood transfusion are the main pitfalls of leeching. Conclusion: Leeches can be considered a salvage method for ear replantation and reattachment in those cases that lack venous outflow in the presence of valid arterial inflow.